Preliminary Outcomes of Different Tactics of Ureteral Stent Placement in Patients with Ureteral Stricture Undergoing Balloon Dilatation: Experience from a Large-Scale Center - Hu, Xiao; Feng, Dechao; Wei, Xin (Frontiers in Surgery, 2022)
Purpose: Our aim is to demonstrate the optimal number of ureteral stent placement in patients with ureteral stricture after balloon dilatation. Methods: A retrospective analysis of 213 patients who underwent balloon dilatation from 2011 to 2019 was conducted. All statistical analyses were completed by the software SPSS 25.0. Results: Of the patients enrolled, 119 were males and 94 were females. The average age was 44.71 years. One month after stent removal, the overall success rate of ureteral stent placement was 76.99%, and the success rate of single, double, and triple stent groups were 81.7%, 70.3%, and 79.3%. Six months after stent removal, the overall success rate was 61.9%, and the success rate of the three groups were 61.7%, 52.7%, and 74.1%. Twelve months after stent removal, the overall success rate was 55.9%, and the success rate of the three groups were 51.9%, 48.6%, and 70.7%. During indwelling the stents, the proportions of severe bladder irritation symptoms in the three groups were 13.6%, 16.2%, and 20.7%. Multivariate analysis indicated the length of US, the time and number of ureteral stent placement were independent risk factors of the treatment effect at six months and twelve months after stent removal. Patients in triple stents group had better prognosis when compared to those in the single or double stents group. Conclusions: The long-term effect of three stents is better than that of single and double stents, but the success rate of treatment reduced gradually over time.